Analysis of Variables Affecting Cassava Chips Production Results in UMKM DF Darungan Village, Selorejo District, Blitar Regency (Agridevina : Berkala Ilmiah Agribisnis, 2022)
This study aims to determine what variables affect the production of cassava chips and determine the variables that affect the production of cassava chips in UMKM DF Darungan Village, Selorejo District, Blitar Regency. The variables contained in this study are capital, labor, and raw materials, these variables that can affect the results of cassava chips production in UMKM DF Darungan Village, Selorejo District, Blitar Regency. The method used in this study is a multiple linear quantitative method. Data collection was carried out for two months at the research site with a predetermined format. The data analysis technique used is the classical assumption test (autocorrelation test, normality test, heteroscedasticity test and multicollinearity test), multiple linear test (t test, f test). The results of the study show that the dependent variable (capital, labor, raw materials) has passed the classical assumption test. Furthermore, the labor variable has a partial effect on the production of cassava chips in UMKM DF. Furthermore, the variables of workers, machines, and raw materials have a simultaneous effect on the production of cassava chips in UMKM DF. DOI : https://doi.org/10.33005/agridevina.v11i2.3479